Determination of the Psychological Resilience Levels of Handball Coaches according to Various Variables - Bulgurcuoglu, Ahmet Nusret (Progress in Nutrition, 2020)
Study Objectives: The study aimed to determine the psychological resilience levels of handball coaches in terms of various variables. Methods: The research group consisted of 114 volunteer coaches (51 women - 63 men) who were in Turkey Handball Federation 2017-2018 season in the national team and displacement handball. In the study, a personal information form, the "Resilience Scale" developed by Friborg et al. (2005) and adapted into Turkish by Çetin and Basım (2011) were used to determine the psychological resilience levels of the participants. Independent Sample t-test and One-way ANOVA analysis were used in the analysis of the data through the SPSS package program. Results: According to the result of the study, a statistically significant difference was found in the social resources sub-dimension according to the level of the coaches and their working time. Conclusion: It was observed that social resources increased depending on the increase in the time spent in coaching and the degree of rank held.